Optical Detection System of Heavy Metals Based on Microplasma Excitation - Tomasz Matusiak; Arkadiusz Dąbrowski; Leszek Golonka (Proceedings)
This paper presents the outcome of a study on the reliability of sensors utilizing microplasma to analyze the amount of selected elements in aqueous solutions. Increasing environmental pollution poses new challenges for protective services through real-time monitoring. The aim of this work was to develop miniature plasma generators for the excitation and then analysis of aqueous solutions.